Application of stabilized biosolids and fly ash mixtures as soil amendments and their impact on free living nematodes and carrot (Daucus carota) yield - Karla E. CortÃ©s-Tello; Michael A Powell (International Journal of Recycling of Organic Waste in Agriculture)
Background: In light of existing regulations regarding the use of nematicides coupled with the global loss of agricultural outputs due to nematodes, new strategies are needed to ensure soil ecosystem health while promoting crop production without the use of potentially dangerous chemicals. Proof of concept methodologies can be used by soil/agricultural scientists interested in identifying potential shortcomings of a given strategy and to identify additional parameters for future work. Using this limited approach allows for the dissemination of information in a stepwise fashion so that changes in research strategies can be initiated prior to final âdefinitiveâ results. This work tests the viability of using coal fly ash, stabilized biosolids, or a mixture of the two to manage plant-parasitic nematode populations and increase carrot yield. Results: The fly ash and biosolids chosen for this work did not alter soil pH or metal content enough to impact significantly on nematode populations. Data on all parameters were combined to see overall trends. The soil and amendments are basic in nature with pH values close to 8 and only fluctuating between 0.2 (season 1) and 0.4 (season 2) pH units from baseline to harvest. Fly ash played a minor role in B and Fe increases, and biosolids contained slightly more Ca, Cu, K, Mg, P, and Zn than the soils, but none of these elements were present in concentrations that affected nematode ontogeny. Fly ash was more important in altering electrical conductivity than biosolids and had the greatest impact on nematode population changes. Biosolids were most important for increasing carrot yields either alone or in mixtures. Conclusions: Not all fly ash or biosolids are equal. The choice of these materials as soil amendments, or natural nematicides, should be based on pre-examination of the soils and the raw materials. Subsequently, ratios and application rates should be chosen so that the physicochemical and microbiological conditions favor nematode management. Biosolids and biosolids mixed with fly ash are capable of enhancing carrot yield significantly at the ratios and application rates tested in this study but had little effect on nematode populations.